108k views
10 votes
Noah says that 9X minus 2X plus 4X is equivalent to 3X because the subtraction sign tells us to subtract everything that comes after 9X

User Joctee
by
4.5k points

1 Answer

8 votes

Answer:

False

Explanation:

It is given that Noah thinks :

9x - 2x + 4x = 3x as the subtraction sign after 9x tells us to subtract everything that comes after 9x.

This is wrong as according to the BODMAS rule, we have to do the addition operation first and then followed by subtraction operation.

That is

⇒ 9x - 2x + 4x

⇒ (9x -2x)+ 4x

⇒ 7x + 4x

⇒ 11x

Therefore the answer to the equation is 11x and not 3x.

User Gberes
by
5.7k points